Implementasi Pengarusutamaan Gender Dalam Rekrutmen dan Promosi Jabatan Stuktural Pada Sekretariat Majelis Permusyawaratan Ulama Aceh - Jannah, Iftitahul; Putri Marzaniar; Muazzinah (Universitas Islam Negeri Raden Intan Lampung, 2025)
This research discusses the complexity of implementing gender mainstreaming in structural positions at the Secretariat of the Aceh Ulama Consultative Assembly, which can provide insight into the dynamics of gender mainstreaming in the bureaucracy and emphasize the importance of structural reform to achieve substantive gender justice. The research method used was qualitative with a single case study approach. Data were collected by semi-structured interviews, direct observation, document analysis, and audiovisual digital materials. A purposive sampling technique was used for informant selection. Data analysis techniques included data collection, data reduction, data presentation, and verification. The research findings show that despite the existence of gender-equitable policies and equal development opportunities among men and women, structural realities still require systemic transformation, which can be seen from the accessibility of information and opportunities for recruitment and promotion, women's participation in decision-making processes at the structural level, control over resources and decisions that influence policies, and justice in obtaining benefits for women. Some barriers include male dominance in the civil service hierarchy and the lack of affirmative policies.